2021
DOI: 10.21070/midwiferia.v7i1.1315
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sule Honey Comsumption in Increasing Milk Production for Working Mothers Using Breastfeeding Pump Method

Abstract: Decreasing milk production is a major problem for working mothers to continue breastfeeding their babies after the maternity leave period is over, besides that the lack of support from people around them, especially family, work place, time to pump breast milk, availability of lactation room greatly affects the consistency of milk production. Breastfeeding mothers need help to make the breastfeeding process more successful, namely by consuming foods that can stimulate milk production. An alternative food ingre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Child development is closely related to how broad parents' understanding and parenting for their children (Baroroh & Maslikhah, 2021). In other words, if the mother's knowledge is good, the better the mother's parenting towards the stimulus of toddler development.…”
Section: Resultsmentioning
confidence: 99%
“…Child development is closely related to how broad parents' understanding and parenting for their children (Baroroh & Maslikhah, 2021). In other words, if the mother's knowledge is good, the better the mother's parenting towards the stimulus of toddler development.…”
Section: Resultsmentioning
confidence: 99%
“…So, this question was raised that honey could have effects on the results and it can be a galactagogue itself. Despite a huge number of studies that show significant effects of natural galactagogues, there is only a study by Baroroh that showed the effectiveness of sule honey consumption in increasing milk production for working mothers [ 23 ]. An animal study also showed an increase in milk production after using honey as a dietary supplement for lactating cows [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Honey is traditionally used in combination with herbal galactagogues [ 22 ]. There is only a study showing the effectiveness of sule honey consumption in increasing milk production of working mothers [ 23 ]. Besides, a study showed an increase in milk production after using honey as a dietary supplement for lactating cows [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Masalah itu antara lain Anemia Defisiensi Besi (ADB) dan Kekurangan Energi Kronis (KEK). Anemia dan KEK pada ibu hamil meningkatkan risiko terjadinya Bayi Berat Lahir Rendah (BBLR), kelahiran prematur, kematian ibu dan bayi dan stunting (anak pendek) (Baroroh et al, 2021).…”
Section: Pendahuluanunclassified